Treaty between Alalakh and Kizzuwatna Kingdoms - al-Ayoubi, Mohammad; Mohammad, Jihan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The city of "Alalakh" was the center of an Kingdom in the northwestern corner of Syria during the 18-14 centuries BC , and enjoy cultural and commercial importance , and built important link with Anatolia . Archaeological Excavations at the site(1937-1949) revealed about 900 written text of cuneiform and Akkadian language , it helps to know the nature of the political, administrative and economic situation in Alalakh, and its foreign relations . Among them a treaty held by the King Idrimi ( 15th century BC) with Pilia the King of Kizzuwatna a neighbors Kingdom to the north , in the regions of Cilicia . It is one of dozens of treaties concluded between the kingdoms of the ancient Near East, major and minor, since the third millennium BC until the first. The Treaty is especially important in several aspects, most notably that pinned between the two kingdoms adjacent were faced with challenges affecting their existence and sovereignty of both.